Future orientation and self-perception minimize risk engagement and promote positive youth development - Jackman, Danielle Marie-Therese, author; MacPhee, David, advisor; Riggs, Nathaniel R., advisor; Youngblade, Lise M., committee member; Harman, Jennifer J., committee member (Colorado State University. Libraries, 2015)
Adolescence is a developmental period marked by physical, cognitive, and social changes that influence both negative behaviors and positive youth development (PYD). Theorists and empirical work have noted that these marked changes propel youth to explore and construct a personal identity. This exploration and commitment of an identity helps to build youths’ self-perceptions as well as refine and orient one’s future. However, for some youth, the adolescent period is considered a time of heightened engagement in health-compromising behaviors. Both risk reduction and strength-based literature identify self-perceptions (self-esteem and self-efficacy) and positive thoughts about the future, which can incorporate a sense of purpose, as factors related to an adolescents’ engagement in risk as well as adolescents’ positive development. However, few studies have highlighted how these factors serve as mediators between these associations. Therefore there were two studies assessed in this dissertation. Study 1 assessed two competing mediational models to determine whether future orientation mediated the relations between self-esteem and adolescent risk or whether self-esteem mediated the relation between future orientation and adolescent risk. I utilized data from an intervention designed to delay sexual debut. Results suggested future orientation to fully mediate the association between self-esteem and adolescent risk. However, self-esteem did not serve as a significant mediator between future orientation and adolescent risk. One limitation could be the assessment of general self-esteem instead of a more domain-specific form of self-esteem. In Study 2, future orientation was assessed as a probable mediator between self-efficacy and PYD. Utilizing a sample of adolescents who served as part of the comparison group for a family and youth leadership program, results found future orientation to partially mediate the relation between self-efficacy and PYD. Several explanations were given for this partial mediation, with a strong emphasis on the conceptual complexity of PYD and dynamic interplay among variables that define PYD as being possible predictors and producers of PYD. Both studies highlight the importance of understanding the quintessential roles that both future orientation and self-perception play in the reduction of adolescent risk and development of a positive youth. In particular, future studies need to continue focusing on the examination of the potential developmental cascade of future orientation as serving as a potential mediator between self-perceptions and adolescent behavior.